Psikoedukasi Keluarga pada Pasangan Suami Istri yang Mengalami Penyakit Kronis - Synthia Andriani; Herni Susanti; Yossie Susanti Eka Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to describe family psychoeducation for married couples who suffer from chronic illnesses. The research method used was a case report conducted at RT 01/RW 09, Tegallega Village, Sempur District, Central Bogor City, on clients with diabetes mellitus with diabetic wounds by providing family psychoeducation in 6 sessions to the primary caregiver over five meetings. The research results showed that the CANSAS assessment found that three types of family needs were unmet. In conclusion, family psychoeducation can be used for husband and wife couples who suffer from chronic diseases by reducing psychological problems and the burden on caregivers in caring for clients with chronic conditions, namely diabetes mellitus. Keywords: Family Psychoeducation, Chronic Illness, Husband and Wife